Carmen - Bizet, Georges (Italy : Pagoda Books/Simon and Schuster, 1987)
In the course of the opera, we see Don José first of all as a naive and unsophisticated man; he discovers love for the first time with Carmen but then he ends by destroying himself. He is a loser, a violent personality who is unable to rise above circumstances. He does not know how to fight against fate.
Keywords: Theatre; Opera; Carmen; Georges Bizet; Opera